Clinico-Radiological Assessment as A Predictor of Difficult Laparoscopic Cholecystectomy - Timilsina, Bishow Deep; Timilsina, Babita Subedi (Journal of National Heart and Lung Society Nepal, 2024)
Background: Laparoscopic cholecystectomy (LC) is the standard treatment for gallstone disease, but predicting difficult cases and conversion to open surgery remains challenging. This study aimed to identify preoperative clinic-radiological factors associated with difficult LC and conversion. Methods: A retrospective cross-sectional study was conducted at the Manipal College of Medical Sciences, Pokhara, including 156 patients who underwent LC from January 2024 to June 2025. Demographic, clinical, laboratory, and ultrasonographic data were analyzed, with p-value11,000/mm³, GB wall >3 mm, pericholecystic collection, and stone size >25 mm (p-value3 mm, pericholecystic collection, stone size >25 mm, and multiple stones (p-value